Connecting beyond ‘Community’: Recasting the Power of Social Capital on Collective Action in Indonesian MSMEs - Hempri Suyatna; Tauchid Komara Yuda (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
The purpose of this article is to look into the functions of community in running capitalism at the micro-level through Micro Small and Medium Enterprises (MSMEs), as well as the effects on the collective well-being of the members. The concept of community-welfare capitalism is used and re-examined in this article. The term “community-welfare capitalism” refers to a form of capitalism that stems from grassroots communities in Indonesia and other Asian countries. Based on our empirical findings on three MSMEs in Yogyakarta, Indonesia, it is argued that, while the majority of works of literature emphasizes the importance of the community in providing informal social protection, our findings confirm that the community's role extends beyond social care to include economic security through collaborative business development. Because Indonesia is currently struggling to achieve inclusive welfare, our conclusion of community-welfare capitalism emphasizes the importance of informal support for social redistribution. As a result, it has been demonstrated that the community-welfare capitalism system, which includes MSMEs, can assist formal welfare institutions in integrating unabsorbed social risk during these difficult times.